High endothelial venule‐like vessels and lymphocyte recruitment in testicular seminoma. (11th February 2014) - Sakai, Y.; Hoshino, H.; Kitazawa, R.; Kobayashi, M.
Summary Seminoma, the most common testicular malignant neoplasm, originates from germ cells and is characterized by the presence of numerous tumour‐infiltrating lymphocytes (TILs). Although it is widely accepted that TILs function in surveillance and cytotoxicity in various tumours including seminoma, detailed mechanisms governing TIL recruitment are not fully understood. It has been shown that high endothelial venule (HEV)‐like vessels are induced in inflamed and neoplastic tissues and contribute to lymphocyte recruitment in a manner similar to the way physiological lymphocyte homing occurs in secondary lymphoid organs. Here, we report that HEV‐like vessels, which express MECA‐79+ 6‐sulfo sialyl Lewis X‐capped structures, are induced in TIL aggregates in seminoma, and that such vessels potentially recruit circulating lymphocytes, as an E‐selectinIgM chimera bound these vessels in a calcium‐dependent manner. These HEV‐like vessels express intercellular adhesion molecule 1 (ICAM‐1), but not vascular cell adhesion molecule 1 (VCAM‐1) or mucosal addressin cell adhesion molecule 1 (MAdCAM‐1), which likely contributes to lymphocyte firm attachment. We also found that the number of T cells attached to the luminal surface of HEV‐like vessels was greater than the number of B cells (p < 0.0001). Interestingly, while CD8+ cytotoxic T lymphocytes (CTLs) attached to the lumen of HEV‐like vessels were scarcely detected, significant numbers of proliferative CTLs were observed outside vessels. These histological findings strongly suggest that TILs, particularly T cells, are recruited to seminoma tissues via HEV‐like vessels, and that tumour‐infiltrating CTLs then undergo proliferation after transmigration through HEV‐like vessels in testicular seminoma.